Effectiveness Of Preoperative Education Using Digital Leaflet And Motion Media On Oncology Surgery Patients' Knowledge Of Surgical Procedures At Pku Muhammadiyah Hospital Yogyakarta - Ayu Ratna Gumilar Ayu; Raden Sugeng Riyadi; Gatot Suparmanto (CV. AFDIFAL MAJU BERKAH, 2026)
Patients' lack of knowledge regarding surgical procedures may lead to anxiety, fear, and unpreparedness in facing surgical interventions. Preoperative education is one of the strategies used to improve patients' understanding and preparedness before surgery. The use of educational media, such as digital leaflets and motion media, is expected to enhance oncology surgery patients' knowledge regarding surgical procedures. This study aimed to determine the effectiveness of preoperative education using digital leaflets and motion media on oncology surgery patients' knowledge of surgical procedures at PKU Muhammadiyah Hospital Yogyakarta. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest with two-group design. A total of 30 respondents were selected using purposive sampling and divided into two groups: the digital leaflet group and the motion media group. Data were collected using an oncology surgery patient knowledge questionnaire and analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test with a significance level of 0.05. The results showed that education using digital leaflet media increased the mean knowledge score from 3.73 ± 1.49 to 5.47 ± 1.25 (p = 0.001). In the motion media group, the mean knowledge score increased from 4.07 ± 1.53 to 6.60 ± 1.40 (p = 0.001). The Mann–Whitney U Test showed a p-value of 0.032, indicating a significant difference in effectiveness between the two educational media. Motion media demonstrated greater improvement in patient knowledge, with a mean rank of 18.87 compared with 12.13 for digital leaflet media. Preoperative education using both digital leaflet and motion media was effective in improving oncology surgery patients' knowledge regarding surgical procedures. However, motion media proved to be more effective than digital leaflets in enhancing patients' understanding of surgical procedures.